The advent of a new trade governance after the omnibus law: Neraca Komoditas - Krisna Gupta; Deasy Pane; Donny Harrison Pasaribu (Center for Indonesian Policy Studies (CIPS), 2022)
The complex nature of Indonesia's export and import policies has led to a lot of challenges in the past. The Neraca Komoditas (NK) scheme might be the solution to address the complicated flow of export-import demand. However, the centralized data distribution and the plan to further expand the list of commodities covered might weaken its effectiveness. This paper discusses policy recommendations to optimize the NK scheme and enable it to overcome the challenges.
Keywords: 330; Außenwirtschaftspolitik; Außenwirtschaftsrecht; Außenhandel; Konzession; Lizenz; Indonesien